2019
DOI: 10.21608/jpp.2019.60672
|View full text |Cite
|
Sign up to set email alerts
|

Improving Rice Grain Quality and Yield of Giza 179 Rice Cultivar Using some Chemical Foliar Spray at Late Growth Stages under Salt Stress

Abstract: Studies were carried in the two seasons of 2017 and 2018 at the Experimental Farm of El-Sirw Agriculture Research Station, Damietta Governorate, Egypt. The main objective of study was to determine the effect of foliar spraying with some chemical substances during panicle initiation+ mid booting stages on rice growth, yield, yield attributes and grains quality characteristics of rice cv. Giza179. The experimental design was performed in randomized complete block design with four replications. Foliar application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
4
2
0
Order By: Relevance
“…Hence, accompaniment K soil application with foliar application in suitable concentration may be maximized utilization efficiency and ensure that the fertilizer synchronizes with plant needs in various stages. These results are in agreement with Awan et al (2007), Metwally and Gharib (2011), Zayed et al (2011) and Okasha et al (2019).…”
Section: E-1-yield Attributessupporting
confidence: 93%
See 1 more Smart Citation
“…Hence, accompaniment K soil application with foliar application in suitable concentration may be maximized utilization efficiency and ensure that the fertilizer synchronizes with plant needs in various stages. These results are in agreement with Awan et al (2007), Metwally and Gharib (2011), Zayed et al (2011) and Okasha et al (2019).…”
Section: E-1-yield Attributessupporting
confidence: 93%
“…Accordingly, a benign accumulation of starch granules was accrued inside grain endosperm and impressive head rice percentage outcomes were going to be a logical result (Wang et al, 2004). These implications were in harmony with Atapattu et al (2018) and Okasha et al (2019). Tables 7 and 8 showed the different responses to various soil and foliar application methods on cooking and eating quality characteristics.…”
Section: E-2-grain Qualitysupporting
confidence: 64%
“…An adequate supply of N, P, and K through foliar application would have increased its uptake and increased the dry matter. These results are in confirmation with the results of Rabin et al (2016) Okasha et al (2019, Begum et al (2018), and Hashem (2019).…”
Section: Rice Yieldsupporting
confidence: 92%
“…This increase might be due to an increase in nitrogen, being the most important plant nutrient, plays a vital role in plant photosynthesis and biomass production, and also influenced cell division and cell elongation. The same trend was observed by Okasha et al (2019) and Jagathjothi et al (2012). The increased photosynthetic pigment efficiency also can contribute to higher LAI, and it is confirmed in the present study through a significant positive correlation between chlorophyll and LAI ( r= 0.946**).…”
Section: Figure 1 Effect Of Foliar Feeding Of Water Soluble Fertilizsupporting
confidence: 87%
“…The best significant grain quality were obtained from (123.75 kg N ha -1 combined with NPK foliar application and 2% N once or twice) and recommended dose (165 kg N ha -1 ) in the two seasons. Okasha et al, (2019) reported that, foliar spray of fertilizer at different growth stages would be recommended for improving rice quality and productivity of Giza 179. Pan et al, (2013) found that, foliar fertilizer application improved the rice grain quality characteristics.…”
Section: Resultsmentioning
confidence: 99%